Wide_area damping controllers of wind and solar power using probabilistic signal selection - Issarachai Ngamroo (My University, 2019)
Recently, renewable energy sources such as wind turbines and solar photovoltaics have been increasingly applied in power systems to support inflated load demands. These renewable sources may be placed at locations that provide higher controllability of inter‐area oscillations than those of conventional synchronous generators. Thus, an improved damping effect from such renewables can be expected. On the other hand, the signal selection of the wide‐area damping controller (WADC) is normally conducted at an operating point. The strength of the input–output pairs of the WADC will consequently change according to the system operations. This study presents a WADC of wind and solar power sources using probabilistic signal selection. After selecting the most suitable input–output pairs, the control parameters of WADC are optimised using a robust control strategy and multiple‐pole placement at several operating points. The designed WADC is evaluated by small‐signal and transient stability studies in the IEEE 50‐machine 145‐bus system to guarantee the stabilising effect of the proposed WADC of wind and solar compared to that of the conventional WADC of synchronous generators.
Keywords: SIGNAL (programming language); Power System Optimization and Stability